Colonoscopy Surveillance after Colorectal Cancer Resection: Recommendations of the US Multi‐Society Task Force on Colorectal Cancer. (March 2016) - Kahi, Charles J; Boland, Richard C; Dominitz, Jason A; Giardiello, Francis M; Johnson, David A; Kaltenbach, Tonya; Lieberman, David; Levin, Theodore R; Robertson, Douglas J; Rex, Douglas K
Abstract : N/A: The US Multi‐Society Task Force has developed updated recommendations to guide health care providers with the surveillance of patients after colorectal cancer (CRC) resection with curative intent. This document is based on a critical review of the literature regarding the role of colonoscopy, flexible sigmoidoscopy, endoscopic ultrasound, fecal testing and CT colonography in this setting. The document addresses the effect of surveillance, with focus on colonoscopy, on patient survival after CRC resection, the appropriate use and timing of colonoscopy for perioperative clearing and for postoperative prevention of metachronous CRC, specific considerations for the detection of local recurrence in the case of rectal cancer, as well as the place of CT colonography and fecal tests in post‐CRC surveillance.